New Media 3.0: Merancang Model Pemberdayaan Komunikasi Politik yang Interaktif - Anang Sujoko (Universitas Muhammadiyah Ponorogo, 2020)
The use of new media in Indonesia significanty grows, especially among the youth generation. Unfortunately, it does not happen in the youth community organization. This study aims to determine the factors that become obstacles for youth community organizations in managing new media for the benefit of the organization. This research is a mixed method by using survey data collection techniques to identify the level of use of new media in each organization and focus group discussion (FGD) to obtain more in-depth data about the problems that become obstacles in its management. This study succeeded in digging data from 15 youth community organizations in the City of Kediri. This research succeeded in mapping the problems experienced by CSOs in utilizing the internet and its interactive platforms. Based on a survey conducted on 15 CSOs, it was found that the main problem faced was the unavailability of qualified human resources in CSOs that were specifically tasked with managing CSO social media accounts. This is also due to the low awareness of CSOs about the potential of the internet and new media 3.0 to treat their political audience. Furthermore, another obstacle faced is the difficulty in producing content. Based on the focus group discussion conducted to follow up on the results, the researcher concluded the two conditions above because CSOs do not have sufficient awareness and knowledge of the potential of the use of the internet and all its interactive platforms for political communication. The conclusion of this study is that the management of new media for organizations has not been taken seriously because of the low level of awareness of the importance of new media for organizational development. However, the design of the digital storytelling concept in order to create a sanse of belongings for the political audience of each community organization is seen as an alternative management solution after the appointment of manager responsibility.